Penerapan Manajemen Risiko Pembiayaan Qardl di Koperasi Konsumen Darul Hikam Syariah Desa Tracal Kecamatan Karanggeneng Kabupaten Lamongan - Livia Suhervi; Khozainul Ulum (Universitas Islam Lamongan, 2022)
Qardl financing is one of outlay product in Darul Hikam Syariah Concumer Cooperative coming through capital lack problems due to many inconsiderate debtors. This subsequently triggers some suspicions about its regulations of risk management applied in qardl financing. This study is qualitative research applying descriptive analysis approach. The data are collected using techniques of observation, interview and documentation. The results reveal several findings. First, the procedure of qardl financing in Darul Hikam Syariah Consumer Cooperative is divided into four stages. They are the submission stage, the analysis stage, the disbursement stage, and the installment stage. In the disbursement stage, an administrative fee is determined based on the loan amount. Second, the qardl financing risk management analysis is not in accordance with the theory. It can be seen from the risk management process which is only carried out by means of identification, measurement, and control. There is no monitoring due to the lack of human resources (employees) in providing assistance, approach, and direct direction for borrowers. Otherwise, the monitoring is crucial in the process of minimizing the occurrence of failed businesses and experiencing bad credit settlement.